2021
DOI: 10.1177/1097184x211017186
|View full text |Cite
|
Sign up to set email alerts
|

Masculinity Attitudes Across Rural, Suburban, and Urban Areas in the United States

Abstract: This article uses the 2011–2019 National Survey of Family Growth to explore how masculinity attitudes differ by rural, suburban, and urban contexts across three social axes: sexual identity, race/ethnicity, and education. It examines within-group differences based on spatial context among 17,944 men aged 15–44 who are straight, gay/bisexual, Black, white, and Latino, as well as among men with less than a bachelor’s, a bachelor’s, and more than a bachelor’s. This contributes to existing knowledge in several way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 55 publications
0
8
1
Order By: Relevance
“…No notable differences were found between rural and urban parents in this study. This is inconsistent with prior research finding more conservative attitudes among rural than urban men; however, a recent study found that this relationship was moderated by the level of education with weaker effects among more educated men (Silva, 2022). As our sample had above-average education levels (66% completed some college), the effects of rural versus urban context on attitudes may have been less evident.…”
Section: Limitations and Future Researchcontrasting
confidence: 99%
“…No notable differences were found between rural and urban parents in this study. This is inconsistent with prior research finding more conservative attitudes among rural than urban men; however, a recent study found that this relationship was moderated by the level of education with weaker effects among more educated men (Silva, 2022). As our sample had above-average education levels (66% completed some college), the effects of rural versus urban context on attitudes may have been less evident.…”
Section: Limitations and Future Researchcontrasting
confidence: 99%
“…2017), these findings are inconsistent with Norton and Herek's (2013) study that focused solely on transgender attitudes wherein rural men and women did not significantly differ in their attitudes toward transgender people. Building from scholarship that has demonstrated that rural men are more likely to endorse conservative attitudes about masculinity (i.e., men have greater sexual needs than women) than urban men (Silva 2022), these findings demonstrate that rural men and women may have qualitatively different experiences that shape their LGBTQ attitudes. It may be that rural men feel particularly embedded in maintaining hetero‐cis‐normativity and consequently, harbor more anti‐LGBTQ perspectives.…”
Section: Discussionmentioning
confidence: 66%
“…People in rural areas are more likely to oppose abortion (Albrecht 2022;Johnson and Scala 2021) and same-sex marriage (Baunach 2012;Sherkat 2017), show ambivalence toward female leaders (Urbatsch 2018), approve of reducing immigration (Johnson and Scala 2021), and exhibit higher rates of racial resentment (Mettler and Brown 2022) compared to their urban counterparts. Furthermore, rural men are more likely to endorse conservative attitudes about masculinity (i.e., men have greater sexual needs than women) than urban men (Silva 2022). Given that research indicates that traits such as traditional religious beliefs, Christian nationalism, and voting Republican are associated with a greater likelihood of stigmatizing LGBTQ individuals (Bills and Hayes 2022;Davis and Perry 2021;Jelen 2017;Worthen et al 2017), we suspect that rural residents, who share many of these traits, are more likely to exhibit stigmatizing attitudes toward LGBTQ individuals when compared to nonrural residents.…”
Section: Rural Americamentioning
confidence: 99%
“…It should also be acknowledged that although hegemonic masculinity was used as a guiding framework for coding the interview data in this study, it may not represent some contemporary views of masculinity, or reflect some of the varying influences on what constitutes masculinity in different contexts. Hegemonic masculinity defines several masculine ideals in traditional, stereotypical ways that may have been more common in previous generations; however, these ideals have more recently been debated (MacLean, Hunt, Smith, & Wyke, 2017;Silva, 2021;White, 2021). Some of these changes in the ways that masculine ideals have been framed include healthier behaviors, such as some men not considering themselves to be reluctant health seekers (White, 2021).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Some of these changes in the ways that masculine ideals have been framed include healthier behaviors, such as some men not considering themselves to be reluctant health seekers (White, 2021). Masculine ideals have also been reported as varying across different spatial contexts, with rural and suburban expression notably different from urban ideals (Silva, 2021). These contemporary views need to be considered when the generalizability of these findings is considered for men of other generations, or those living in different spatial contexts.…”
Section: Strengths and Limitationsmentioning
confidence: 99%